Study of the Spin-Memory Effect with low-energy gamma-rays in 177Hf(n,γ)178Hf reaction measurement - Kawamura Shiori; Endo Shunsuke; Iwamoto Osamu; Iwamoto Nobuyuki; Kimura Atsushi; Kitaguchi Masaaki; Nakamura Shoji; Okudaira Takuya; Rovira Gerard; Shimizu Hirohiko; Shima Tatsushi; Yoshikawa Hiromoto (EPJ Web of Conferences)
A method on the basis of the Spin-Memory Effect (SME) is available to measure the total angular momentum J of a resonance in a neutron capture reaction. This method uses the fact that the intensity ratio of two gamma-rays emitted from a resonance depends on the J of the resonance. In this study, neutron capture reaction measurements were performed at J-PARC MLF ANNRI using natural Hf (atomic number Z = 72). The total angular momentum of six resonances is deduced. The strength of SME was determined from those analyses. It was found that SME observed in resonances of 177Hf was stronger than that expected in past studies.